Pemanfaatan Kecerdasan Buatan dan Otomatisasi untuk Inovasi Administrasi Pendidikan - Ibnu Hajar; Emay Rahmayani (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the utilization of artificial intelligence (AI) and automation in educational administration, focusing on supporting factors, challenges, as well as their impacts and implications on the efficiency and quality of educational services. A qualitative method with a literature review approach was employed, analyzing various academic sources and policy documents. The findings indicate that AI and automation can accelerate administrative processes, enhance data accuracy, and support data-driven decision-making. Successful implementation is influenced by infrastructure readiness, staff competence, management support, adaptive organizational culture, data quality, and stakeholder engagement, while major obstacles include limited human resources, costs, security risks, resistance to change, and integration with legacy systems. This study emphasizes the importance of a holistic strategy, including staff training and security protocols, to optimize technological benefits and achieve an efficient, accurate, and adaptive educational administration system.